Global Health: Issues and Challenges - Shinu KURIAKOSE (Modern Medicine)
The challenges facing global health continue to evolve and will very soon emerge as an emergent problem due to the various conditions which fuel this issues. The combination of increased population, ageing which is more focused currently on quantity versus quality of life, chronic hunger issues, lack of clean drinking water puts a combined pressure on the resources we possess to a breaking point. It is imperative that developed countries with the assistance of non-governmental organizations take the lead in educating underdeveloped countries and entities into initiating sustainable practices, which will help, control the various challenges for global health with a long-term view of eliminating these obstacles. There needs to be investments made in harvesting clean water, implementing sustainable farming practicing, providing micro-loans to access funds and an improved focus on birth control practices. As the population continues to grow, access to resources will continue to be limited and only available to the rich and wealthy; a scenario, which will only lead to, increased potential of global calamity.